Remediation of Lead-Contaminated Water by Red Yeast and Different Types of Phosphate - Tian, Da; Cheng, Xiaohui; Wang, Liyan; Hu, Jun; Zhou, Ningning; Xia, Jingjing; Xu, Meiyue; Zhang, Liangliang; Gao, Hongjian; Ye, Xinxin; Zhang, Chaochun (Frontiers in Bioengineering and Biotechnology, 2022)
Rhodotorula mucilaginosa (Rho) can secrete large amounts of extracellular polymeric substances (EPS) to resist lead (Pb) toxicity. Phosphate is an effective material for the remediation of Pb. This study explored the Pb remediation by the combination of Rho and different types of phosphate in water. To do so, four phosphates, i.e., ferric phosphate (FePO4, Fe-P), aluminium phosphate (AlPO4, Al-P), calcium phosphate (Ca3(PO4)2, Ca-P) and phosphogypsum (PG) were employed along with Rho. Compared with Rho application along, the addition of phosphate significantly promoted the secretion of EPS by Rho (21-25 mg vs. 16 mg). The formed EPS-Pb contributes to the Pb immobilization in the combination of Rho and phosphate. After six days of incubation, Rho+phosphate treatments immobilized over 98% of Pb cations, significantly higher than Rho treatment (94%). Of all Rho+phosphate treatments, Ca-P and PG-amended Rho had higher secretion of EPS, resulting in higher Pb removal. Nevertheless, PG had the highest efficiency for Pb removal compared with other phosphates, reached to 99.9% after six days of incubation. Likewise, new Pb minerals, i.e., pyromorphite and lead sulfate only appeared in Rho+PG treatment. Altogether, this study concludes on the combined application of Rho and phosphate as an efficient approach to promote Pb remediation, particularly using PG waste.